Digital Marketing Adoption Among Small Businesses in Dhaka: A Case Study of Stamford University Graduates - Mohammad Fakhrul Islam (Journal of Educational Studies, 2025)
The rapid advancement of digital technologies has redefined marketing practices across the globe, with small businesses increasingly embracing digital platforms to enhance market presence, customer engagement, and operational efficiency. This study investigates the extent and nature of digital marketing adoption among Stamford University graduates operating small businesses in Dhaka, Bangladesh. Using a mixed-methods approach, data were collected through a structured .questionnaire (n = 30) and in-depth semi-structured interviews (n = 10). The findings provide insight into the tools used, perceived benefits, implementation challenges, and the influence of academic background on digital marketing behavior. The study revealed that 83% of participants had adopted at least one form of digital marketing, with social media platforms—particularly Facebook (90%) and Instagram (65%)—being the most widely used. However, more advanced tools such as SEO (28%), Google Ads (20%), and email marketing (15%) were considerably underutilized. While 76% of respondents reported improved customer reach and 69% noted enhanced brand visibility, only 41% observed a significant impact on direct sales. Key challenges included limited technical skills (reported by over 60%), time constraints (45%), and a lack of understanding regarding return on investment. Though participants credited their Stamford University education with providing strong theoretical foundations, 62% acknowledged that practical digital marketing skills were largely self-taught. The research highlights a notable curriculum-practice gap and underscores the need for practical digital literacy training within business education programs. These findings contribute to the broader discourse on SME digital transformation in emerging economies and emphasize the importance of institutional and educational support in enabling effective digital marketing adoption